Muslim Family Methods on the Negative Impact of Digital Technology Advances in the Era of Industry 4.0 on Children Aged 4-7 in Surakarta - Azizah, Annafi Nurul Ilmi; Wardani, Anita; Nashir, Muhammad Jafar (Suhuf: International Journal of Islamic Studies, 2024)
The impact of technology on people's lives is enormous, because of the impact of social change that is felt by the whole layer of society, both in the city and in the countryside, not only among adults but also among early children. If the use of technology is inappropriate, then it will bring problems to the lives of the community and in particular make the old people. The study aims to learn about the Muslim family methods regarding the impact of technological advances in the era of Industry 4.0 on early childhood in Surakarta. The method used in this research is qualitative descriptive which includes data reduction, data display, and conclusion. The study finds that the methods applied by the majority of 10 Muslim families regarding the negative impact of digital technology advances in the era of Industry 4.0 on children aged 4-7 in Surakarta, are preventive methods, methods of surveillance, freeing children to play outdoors with peers, selective in choosing appropriate applications for children, being a good example for kids, and giving time limits for children to use technology. In conclusion, this research illuminates the proactive steps taken by Muslim families in Surakarta to navigate the challenges posed by technological advancements. By adopting a range of preventive measures and promoting a balanced approach, these families strive to ensure a positive impact on the lives of their early childhood members amidst the ever-evolving landscape of Industry 4.0.